Physical exercise regulates p53 activity targeting SCO2 and increases mitochondrial COX biogenesis in cardiac muscle with age. - Zhengtang Qi (Public Library of Science (PLoS), 2011)
The purpose of this study was to outline the timelines of mitochondrial function, oxidative stress and cytochrome c oxidase complex (COX) biogenesis in cardiac muscle with age, and to evaluate whether and how these age-related changes were attenuated by exercise. ICR/CD-1 mice were treated with pifithrin-μ (PFTμ), sacrificed and studied at different ages; ICR/CD-1 mice at younger or older ages were randomized to endurance treadmill running and sedentary conditions. The results showed that mRNA expression of p53 and its protein levels in mitochondria increased with age in cardiac muscle, accompanied by increased mitochondrial oxidative stress, reduced expression of COX subunits and assembly proteins, and decreased expression of most markers in mitochondrial biogenesis. Most of these age-related changes including p53 activity targeting cytochrome oxidase deficient homolog 2 (SCO2), p53 translocation to mitochondria and COX biogenesis were attenuated by exercise in older mice. PFTμ, an inhibitor blocking p53 translocation to mitochondria, increased COX biogenesis in older mice, but not in young mice. Our data suggest that physical exercise attenuates age-related changes in mitochondrial COX biogenesis and p53 activity targeting SCO2 and mitochondria, and thereby induces antisenescent and protective effects in cardiac muscle.